International economics - Appleyard, Dennis R.; Field, Alfred J. (Boston : Irwin/McGraw-Hill, 1998)
The book examines how international transactions influence such things as social welfare, income distribution, employment, growth, and price stability, and the possible ways public policy can affect the outcomes.
Includes bibliographical references (p. 715-736) and index.
rua 26/02/15
Loans
Keywords: International trade; International economic relations; International finance